Ahlul Bait in the Qur'an: Tafsir Ath-Thabari in the Perspective of Hermeneutics Nasr Hamid Abu Zayd - Riski Suriani Lubis; Romlah Widiyati (Jurnal El-Thawalib, 2026)
This study aims to examine the meaning of Ahlul Bait in the Qur’an through a comparative analysis between the classical exegesis of al-Ṭabarī and the critical hermeneutical approach of Nasr Hamid Abu Zayd. This research is qualitative in nature and employs a library research method, using content analysis and critical hermeneutics as its analytical approaches. The data sources consist of primary data, namely al-Ṭabarī’s Jāmi‘ al-Bayān ‘an Ta’wīl Āy al-Qur’ān and the works of Nasr Hamid Abu Zayd, as well as secondary data from tafsir literature and contemporary hermeneutical studies. Data were collected through documentation by identifying and classifying Qur’anic verses related to Ahlul Bait. The data analysis was conducted by examining al-Ṭabarī’s interpretation based on the riwāyah approach and comparing it with Abu Zayd’s hermeneutical framework to reveal the relationship between text, context, and reader. The findings indicate that al-Ṭabarī’s interpretation reflects Sunni theological constructs shaped by historical and socio-political contexts, while Abu Zayd’s hermeneutics opens broader possibilities for reinterpretation. This study concludes that the meaning of Ahlul Bait is dynamic, not merely genealogical, but also represents ethical and spiritual values.